2020
DOI: 10.3389/fmicb.2020.615860
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Enzymes and How They Support Virulence in Pathogenic Bacteria

Abstract: Mononuclear molybdoenzymes are highly versatile catalysts that occur in organisms in all domains of life, where they mediate essential cellular functions such as energy generation and detoxification reactions. Molybdoenzymes are particularly abundant in bacteria, where over 50 distinct types of enzymes have been identified to date. In bacterial pathogens, all aspects of molybdoenzyme biology such as molybdate uptake, cofactor biosynthesis, and function of the enzymes themselves, have been shown to affect fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 256 publications
(424 reference statements)
3
46
0
1
Order By: Relevance
“…One of the most common types of biomolecular damage caused by oxidative stress is the oxidation of sulfur compounds including amino acids. Both cysteine and methionine are highly susceptible to oxidative damage, and there is increasing evidence that both thiol-based and molybdenum-containing methionine sulfoxide reductases protect bacterial pathogens from hostinduced oxidative stress and thus support bacterial virulence (Ezraty et al, 2005(Ezraty et al, , 2017Denkel et al, 2013;Nasreen et al, 2020;Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common types of biomolecular damage caused by oxidative stress is the oxidation of sulfur compounds including amino acids. Both cysteine and methionine are highly susceptible to oxidative damage, and there is increasing evidence that both thiol-based and molybdenum-containing methionine sulfoxide reductases protect bacterial pathogens from hostinduced oxidative stress and thus support bacterial virulence (Ezraty et al, 2005(Ezraty et al, , 2017Denkel et al, 2013;Nasreen et al, 2020;Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous reports indicate that energy generation defects are one of the two major physiological impacts caused by dysfunctional DMSOR molybdoenzymes (Zhong et al, 2020). Our RNA-seq analysis identified that GlnA, an indicator of nitrogen availability, was upregulated in the mobA mutant (Table S1), suggesting nitrogen limitation.…”
Section: Discussionmentioning
confidence: 58%
“…Defects in bis-MGD biosynthesis extensively impact the transcriptome and UPEC fitness in vivo. Given that DMSOR occurs only in prokaryotes (e.g., dissimilatory nitrate reductase and formate dehydrogenase; Zhong et al, 2020), our study has provided potential drug targets for treating UPEC infections.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial dependency of fitness effects of genes on environmental niches has been well documented in studies of antibiotic resistance genes and metabolic enzymes (Zhong et al, 2020, Melnyk et al, 2015). There are three possible outcomes for how the environment shapes the DFEs of newly transferred genes.…”
Section: Resultsmentioning
confidence: 99%